Assessing Intercultural Competence in Experiential Learning Abroad : Lessons for Educators - Paras, Andrea; Mitchell , Lynne (Experiential Learning and Teaching in Higher Education, 2022)
The old adage that travel broadens the mind may not hold true for every student studying abroad. While pre-departure and in-country support for intercultural learning can help, some students still fail to develop their intercultural competence and some even go backwards. Using a combination of quantitative (Intercultural Development Inventory) and qualitative measures, this study examines what happens in intercultural learning when students participated in a four-week experiential field school in India, preceded by a twelve-week preparation course on the ethics of international voluntourism. Results found that, while students’ pre- and post-trip Intercultural Development Inventory results varied, qualitative data gave insights into student learning and revealed important lessons for educators.